2001
DOI: 10.1183/09031936.01.17202060
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of self-management in asthmatics: a 1-yr follow-up randomized, controlled trial

Abstract: Patient education in asthma can improve outcome but cost-effectiveness has not been widely assessed. The aim of the present study was to carry out a cost-effectiveness analysis of patient education in asthmatics in a 12-month follow-up.The authors randomly allocated 78 asthmatics to a control or intervention group after they had received ordinary outpatient consultation care. Intervention consisted of two 2-h group sessions followed by 1–2 individual sessions administered by a nurse and a physiotherapist. Self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
3

Year Published

2002
2002
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 19 publications
(22 reference statements)
3
41
0
3
Order By: Relevance
“…The economical consequences of these interventions were inconclusive. Some of these studies reported a cost reduction [10,12,22,23], whilst others found that extra investments were needed to achieve a reduction in healthcare utilisation of the patients [24,25]. In these studies, however, the asthma nurse intervention was additional to the routine medical care.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The economical consequences of these interventions were inconclusive. Some of these studies reported a cost reduction [10,12,22,23], whilst others found that extra investments were needed to achieve a reduction in healthcare utilisation of the patients [24,25]. In these studies, however, the asthma nurse intervention was additional to the routine medical care.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, maintenance treatment with inhaled corticosteroids has been shown to be cost effective [19][20][21]. The consequences of intervention by asthma nurses on healthcare costs are, however, inconclusive [10,12,[22][23][24][25]. This may be due to the fact that until now, care provided by an asthma nurse has always been additional to routine medical care.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have had relatively small sample sizes, selected cohorts, use of historical control subjects, or ignored the impact of such a program on healthcare costs (8)(9)(10)(11)(12)(13)(14)(15)(16). Some of these studies, but not all, have demonstrated a beneficial effect on healthcare use and asthma knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Utilising a measure of corticosteroid inhaler compliance based on the ratio of dispensed to prescribed therapy over a 12-month period, the median compliance in the self-management group was 82% compared with 55% in the control group. This greater level of compliance was associated with an improved clinical outcome [11] and was cost-effective [17].…”
Section: Which Components Of the Plan Contribute To Its Efficacy?mentioning
confidence: 97%